2022
DOI: 10.1111/jne.13202
|View full text |Cite
|
Sign up to set email alerts
|

Nucleus of the lateral olfactory tract: A hub linking the water homeostasis‐associated supraoptic nucleus‐arginine vasopressin circuit and neocortical regions to promote social behavior under osmotic challenge

Abstract: Homeostatic challenges may alter the drive for social interaction. The neural activity that prompts this motivation remains poorly understood. In the present study, we identify direct projections from the hypothalamic supraoptic nucleus to the cortico‐amygdalar nucleus of the lateral olfactory tract (NLOT). Dual in situ hybridization with probes for pituitary adenylate cyclase‐activating polypeptide (PACAP), as well as vesicular glutamate transporter (VGLUT)1, VGLUT2, V1a and V1b, revealed a population of vaso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Connections between hypothalamic AVP-MCNs and other brain areas involved in stress coping and emotional/motivational behaviors have been demonstrated, through the employment of techniques such as juxtacellular labeling and tract-tracing methods combined with brain serial sectioning in cutting planes at coronal, sagittal, septo-temporal oblique and horizontal orientations. Histochemical reaction against neurobiotin, immunohistochemistry (IHC) against antigens of interest and systematic neuroanatomical analyses were performed (Zhang and Hernandez 2013, Hernandez, Vazquez-Juarez et al 2015, Hernandez, Hernandez et al 2016, Zhang, Hernandez et al 2016, Campos-Lira, Kelly et al 2018, Hernandez-Perez, Hernandez et al 2019, Hernandez-Perez, Hernandez et al 2022). During these studies, a collateral observation was repeatedly made: AVP immunoreactive (AVP-ir) magnocellular neurons seemed to be dispersed from the above-mentioned loci to adjacent subcortical regions.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Connections between hypothalamic AVP-MCNs and other brain areas involved in stress coping and emotional/motivational behaviors have been demonstrated, through the employment of techniques such as juxtacellular labeling and tract-tracing methods combined with brain serial sectioning in cutting planes at coronal, sagittal, septo-temporal oblique and horizontal orientations. Histochemical reaction against neurobiotin, immunohistochemistry (IHC) against antigens of interest and systematic neuroanatomical analyses were performed (Zhang and Hernandez 2013, Hernandez, Vazquez-Juarez et al 2015, Hernandez, Hernandez et al 2016, Zhang, Hernandez et al 2016, Campos-Lira, Kelly et al 2018, Hernandez-Perez, Hernandez et al 2019, Hernandez-Perez, Hernandez et al 2022). During these studies, a collateral observation was repeatedly made: AVP immunoreactive (AVP-ir) magnocellular neurons seemed to be dispersed from the above-mentioned loci to adjacent subcortical regions.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…With the observations mentioned above, we then asked if neurogenesis could be modified as an allostatic mechanism for stress adaptation. AVP-MNNs are able to respond to homeostatic challenges by increasing their metabolic activity generating physiological changes in dehydrated rats (Zhang, Hernandez et al 2016, Zhang, Hernandez et al 2018, Hernandez-Perez, Hernandez et al 2022. A recent comprehensive transcriptomic study has reported change of 2247 RNA transcripts, including Ephrin receptor 6, a gene related to adult neurogenesis, in the SON of Wistar Han rats, after 3 days of water deprivation (Pauza, Mecawi et al 2021).…”
Section: Neurogenesis Occurs Within the Adult Son And Pvn And Osmotic...mentioning
confidence: 99%
“…Second, odor responses in NLOT are strongly influenced by odor valence (Tanisumi et al, 2021), similarly to the olfactory tubercle (OT) (Gadziola et al, 2015; Millman and Murthy, 2020). Third, perturbation of NLOT activity affects social behavior in rats, that is known to rely on olfaction and be affected by emotional state (Hernández-Pérez et al, 2022). Lastly, NLOT neurons show marked transcriptomic changes following fear conditioning (Hochgerner et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Layer 2 contains most of NLOT neurons. However, unlike PC, layer 2 neurons are almost exclusively glutamatergic, pyramidal-like neurons (McDonald, 1983; Millhouse and Uemura-Sumi, 1985; Hernández-Pérez et al, 2022). These send their apical dendrites ventrally into layer 1 where they branch and form synaptic connections with olfactory bulb mitral cell axons.…”
Section: Introductionmentioning
confidence: 99%
“…everyone at the conference in efforts aimed at overcoming intellectual dead-ends, creating new conceptualizations for regulatory peptide research, and promoting international collaborations for solving common problems with complementary expertise and technology. The Hernandez-Perez et al 1 provide a novel example of how two neuropeptides, vasopressin and pituitary adenylate cyclase-activating polypeptide (PACAP), interact to transmit prosocial need when the organism is under homeostatic challenge, by a circuit from the hypothalamus to the cortex via a 'hub' in the amygdaloid complex. In line with this, Peles et al 2 provide new evidence on shaping of the regulatory peptide architecture and action within the stress axis in the adult zebrafish, and what can be learned with this versatile model organism.…”
mentioning
confidence: 99%